Identification of anticancer drugs associated with atrial fibrillation: analysis of the WHO pharmacovigilance database. Issue 4 (30th April 2020) - Alexandre, Joachim; Salem, Joe-Elie; Moslehi, Javid; Sassier, Marion; Ropert, Camille; Cautela, Jennifer; Thuny, Franck; Ederhy, Stéphane; Cohen, Ariel; Damaj, Ghandi; Vilque, Jean-Pierre; Plane, Anne-Flore; et al.
Abstract: Aims: The explosion of novel anticancer therapies has meant emergence of cardiotoxicity signals including atrial fibrillation (AF). Reliable data concerning the liability of anticancer drugs in inducing AF are scarce. Using the World Health Organization individual case safety report database, VigiBase ®, we aimed to determine the association between anticancer drugs and AF. Methods and results: A disproportionality analysis evaluating the multivariable-adjusted reporting odds ratios for AF with their 99.97% confidence intervals was performed for 176 U.S. Food and Drug Administration (FDA)- or European Medicines Agency (EMA)-labelled anticancer drugs in VigiBase ®, followed by a descriptive analysis of AF cases for the anticancer drugs identified in VigiBase ® . ClinicalTrial registration number: NCT03530215. A total of 11 757 AF cases associated with at least one anticancer drug were identified in VigiBase ® of which 95.8% were deemed serious. Nineteen anticancer drugs were significantly associated with AF of which 14 (74%) are used in haematologic malignancies and 9 (45%) represented new AF associations not previously confirmed in literature including immunomodulating agents (lenalidomide, pomalidomide), several kinase inhibitors (nilotinib, ponatinib, midostaurin), antimetabolites (azacytidine, clofarabine), docetaxel (taxane), and obinutuzumab, an anti-CD20 monoclonal antibody. Conclusion: Although cancer malignancy itself may generate AF, we identified 19 anticancer drugs significantly associated with a significant increase in AF over-reporting. This pharmacovigilance study provides evidence that anticancer drugs themselves could represent independent risk factors for AF development. Dedicated prospective clinical trials are now required to confirm these 19 associations. This list of suspected anticancer drugs should be known by physicians when confronted to AF in cancer patients, particularly in case of haematologic malignancies.